Anti-Innovation Norms - Laura G. Pedraza-Fariña (2018)
Intellectual property (IP) scholars have recently turned their attention to social norms—informal rules that emerge from and are enforced by nonhierarchically organized social forces—as a promising way to spur innovation in communities as diverse as the fashion industry and the open-source software movement. The narrative that has emerged celebrates social norms’ ability to solve IP’s free-rider problem without incurring IP’s costs. But this account does not fully consider the dark side of social norms. In fact, certain social norms, when overenforced, can create substantial barriers to the most socially beneficial creative pursuits. Because IP scholars have left unexplored how social norms can hinder innovation in this way, the harm they cause has gone unmitigated. This Article sheds light on the dark side of innovation norms. It coins the term “anti-innovation norms” to label these counterproductive social forces. Using the double lens of sociology and psychology, it gives a full theoretical account of three types of anti-innovation norms: research priority, methodology, and evaluation norms—all of which interfere with socially beneficial boundary-crossing innovation. Our elucidation of anti-innovation norms has both theoretical and policy implications. On the theory side, it suggests that IP scholars to date have been too focused on addressing the free-rider problem. This has caused them to overlook other barriers to innovation, like those posed by the set of anti-innovation norms we describe here. This focus on free riding may also help explain why innovation and norms scholars have paid little attention to debates within the broader literature on law and social norms concerned with identifying situations in which social norms are welfare reducing. On the policy side, it points to innovation dilemmas that IP is not fully equipped to solve. While changes to the IP doctrines of attribution and fair use in copyright and nonobviousness in patent law can counteract anti-innovation norms at the margin, a comprehensive solution requires innovation scholars to broaden their vision beyond the IP toolkit. We take the first steps in this direction, proposing a number of interventions, including novel funding regimes and tax credits